Organic solar cells : fundamentals, devices, and upscaling - Rand, Barry P.; Richter, Henning (CRC Press, Taylor & Francis Group, 2014)
Organic photovoltaic (OPV) cells have the potential to make a significant contribution to the increasing energy needs of the future. In this book, 15 chapters written by selected experts explore the required characteristics of components present in an OPV device, such as transparent electrodes, electron- and hole-conducting layers, as well as electron donor and acceptor materials. Design, preparation, and evaluation of these materials targeting highest performance are discussed. This includes contributions on modeling down to the molecular level to device-level electrical and optical testin.